2021
DOI: 10.1002/bem.22336
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Low‐Frequency Electromagnetic Fields Entrain Locust Wingbeats

Abstract: Extremely low-frequency electromagnetic fields (ELF EMFs) have been shown to impact the behavior and physiology of insects. Recent studies have highlighted the need for more research to determine more specifically how they affect flying insects. Here, we ask how locust flight is affected by acute exposure to 50 Hz EMFs. We analyzed the flights of individual locusts tethered between a pair of copper wire coils generating EMFs of various frequency using high-speed video recording. The mean wingbeat frequency of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…These results were consistent with the results of Shepherd et al [2021], where exposure of bees and pesticides to MF revealed no evidence of synergy between clothianidin and extremely low‐frequency electromagnetic fields (ELF‐EMFs) as environmental stressors, but there is a potential for EMFs to affect the same susceptible fraction of the bee population that has been affected by clothianidin. Moreover, Shepherd pointed out that the results lay the foundation to further explore the interactions of ELF‐EMFs with other environmental stressors and consider the key factors that may make bees susceptible to ELF‐EMFs.…”
Section: Discussionsupporting
confidence: 92%
“…These results were consistent with the results of Shepherd et al [2021], where exposure of bees and pesticides to MF revealed no evidence of synergy between clothianidin and extremely low‐frequency electromagnetic fields (ELF‐EMFs) as environmental stressors, but there is a potential for EMFs to affect the same susceptible fraction of the bee population that has been affected by clothianidin. Moreover, Shepherd pointed out that the results lay the foundation to further explore the interactions of ELF‐EMFs with other environmental stressors and consider the key factors that may make bees susceptible to ELF‐EMFs.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have focused on the walking and questing behavior of ticks in dry versus humid conditions, as air humidity is the key factor for tick activity and survival [23,24]. Few authors have focused on the effect of extremely low EMF frequencies on insects' walking behavior [25][26][27]. Wyszkovska et al showed that exposure to relatively high levels of extremely low frequencies of EMFs, generated by overhead power transmission lines, affects the behavior, neuronal and muscular responses and levels of heat shock protein in the desert locust.…”
Section: Discussionmentioning
confidence: 99%
“…Shepherd et al [ 16 ], by tethered flight experiments on honeybees, showed that during exposure to 0.1 mT, 1.0 mT, and 7.0 mT MF, wingbeat frequency was increased, with a greater effect at higher exposure levels. The influence of MF on wingbeat frequency has also been demonstrated in locust [ 31 ]. A static 50 mT MF modulated the motor behavior of Tenebrio molitor and T. obscurus , but interestingly, even in such closely related species, the effects were remoted [ 32 ].…”
Section: Discussionmentioning
confidence: 99%